A Semiotic Reading of Connotative Meaning in the Lyrics of Song "Monokrom" by Tulus: Reflections on Identity and Nostalgia: - M. Habib Kusnadi (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to uncover the connotative meaning in the lyrics of the song "Monokrom" by Tulus through Roland Barthes' semiotic approach. This song was chosen because it presents a strong nostalgic nuance and reflection of identity, and is full of color symbolism and poetic language. The research method used is a literature study with a descriptive qualitative approach. The data in this study are in the form of words, phrases, clauses, or sentences in the lyrics of the song "Monokrom" by Tulus. The data collection technique was carried out by knowing and searching for the type of literature needed, reading and reviewing the literature, collecting and recording data, and presenting the data. The data analysis technique was carried out using content analysis techniques by analyzing the text of the song lyrics "Monokrom" by paying attention to linguistic signs such as words, phrases, and metaphors that have the potential to have connotative meanings. The results of the study show that "Monokrom" represents gratitude and appreciation for the past through black and white symbols that depict the balance between joy and sorrow. This song also displays a reflection of self-identity, where past experiences play an important role in shaping emotional and spiritual maturity. Through the use of metaphors, color symbols, and a gentle style of language, Tulus successfully conveys a universal message about the appreciation of memories and the importance of social relationships in building human identity. This research confirms that Barthes's semiotics is effective in reading connotative meaning in musical works because it can reveal the relationship between language, culture, and emotional experience.